International environmental agreements in the presence of adaptation - Walid Marrouch; Amrita Ray Chaudhuri (Fondazione Eni Enrico Mattei (FEEM), 2011)
We show that adaptive measures undertaken by countries in the face of climate change, apart from directly reducing the damage caused by climate change, may also indirectly mitigate greenhouse gas emissions by increasing the stable size of international agreements on emission reductions. Moreover, we show that the more effective the adaptive measure in terms of reducing the marginal damage from emissions, the larger the stable size of the international environmental agreement. In addition, we show that larger coalitions, in the presence of adaptation, may lead to lower global emission levels and higher welfare.
Keywords: Q54; Q59; 330; International Environmental Agreements; Adaptation; Coalition Formation; Climate Change